Intensive Care Solely to Facilitate Organ Donation—New Challenges. Issue 8 (August 2017) - Opdam, Helen
Abstract : A discussion of the ethical, legal, community and medical issues of providing intensive care to patients in whom brain death may develop but where physiological supportive treatment is withdrawn or not instituted, for the sole purpose of facilitating organ donation.